Acquired von Willebrand factor deficiency caused by LVAD is ADAMTS-13 and platelet dependent. (January 2016) - Jilma-Stohlawetz, Petra; Quehenberger, Peter; Schima, Heinrich; Stoiber, Martin; Knöbl, Paul; Steinlechner, Barbara; Felli, Alessia; Jilma, Bernd
Abstract: Introduction: The high shear rates induced by left ventricular assist devices cause acquired von Willebrand disease (aVWD). We hypothesised that an ex vivo model could be established to study whether mechanical shear stress alone causes aVWD or whether this process depends also on the VWF cleavage protein ADAMTS-13 and on platelets. Materials and methods: Healthy volunteers and two patients with congenital ADAMTS-13 deficiency donated blood. In vitro closed extracorporeal circuits were established using medically approved left ventricular assist devices (LVAD). VWF multimers were quantified by gel electrophoresis; VWF antigen, ristocetin cofactor activity (VWF:RCo), ADAMTS-13 levels and platelet function were assessed. Results: The high shear stress in the extracorporeal circulation rapidly decreased VWF:RCo and thereby the VWF:RCo/VWF:Ag ratio by 47% (p < 0.01) to pathologically low values. Concomitantly, high molecular weight multimers (HMWM) decreased: up to 14–15 mers were visible on the gels at baseline, which were reduced by a maximum of 6–7 mers, corresponding to an average 68% lower densitometry signal of HMWM (p < 0.001). This was accompanied by marked reduction of aggregation by various agonists (p < 0.005). In contrast, the two patients with congenital thrombocytopenic purpura with virtually complete deficiency of ADAMTS-13 activity had only a minimal or no decrease in multimers (p < 0.005 vs. healthy controls). Similarly, no or minimal depletion of large multimers occurred, when normal plasma circulated without platelets. Conclusion: An in vitro model for LVAD associated aVWD demonstrated that ADAMTS-13 and platelets contribute to the depletion of HMWM of VWF. Highlights: An in-vitro model for left ventricular assist device induces aVWD. ADAMTS-13 is essential for the depletion of HMWM of VWF in aVWD. Platelets are essential for the depletion of HMWM of VWF in aVWD.